Pengembangan Lembar Kegiatan Siswa (LKS) Berbasis Metode Penemuan Terbimbing untuk Meningkatkan Kemampuan Pemahaman Konsep Matematik Siswa Kelas VII SMP Islam Kepenuhan Kabupaten Rokan Hulu - Annajmi Annajmi; Azmi Asra (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2017)
The purpose of this research was to produce a student activity sheet based guided discovery me-thod to improve understanding of the mathematical concept of junior high school students, determine the effectiveness and increase the ability of understanding mathematical concepts that students use the worksheet-based method of guided discovery. The method used was the development of research de-velopment model 4-D, that was define, design, develop and disseminate. The research was conducted in SMP Islam Kepenuhan of Rokan Hulu Riau with research subjects grade VIIIA. Student activity sheet and research instruments validated to the experts, then conducted limited field trial, resulting in the final and disseminate is the use of student activity sheet that has been developed on a broader scale, to subject teachers school math test field try to use this device. The results of the implementation of the trials showed Student Activity Sheet effective to use, as shown by an increase in the ability of students' understanding of the concept, where students in classical completeness there are 30 students who reached the KKM ≥ 70 ie 83.33% of the proceeds from the pretest posttest whereas only 23 those students who completed ie 63.88%, further capabilities increase student understanding of the concept of before and after learning that the average pretest results and the ability of understanding the con-cept 69.84 average yield of 81.35 posttest understanding of the concept. Based on the analysis of data, it is advisable to use a math teacher to student activity sheet based methods guided discovery learning.